THE EFFECT OF DEBT, FIRM SIZE AND LIQUIDITY ON INVESTMENT CASH FLOW SENSITIVITY OF LISTED COMPANIES IN TEHRAN STOCK EXCHANGE (Singaporean Journal of Business Economics and Management, 2015)
This study examines the relationship between some variables (debt, firm size and liquidity), the cash flow sensitivity of investment companies listed in Tehran Stock Exchange, will be examined. Specifically, this study aimed to investigate the hypothesis that the cash flow sensitivity of investment In order to investigate this objective, three main hypotheses and selecting the 100 companies among the listed companies in Tehran Stock Exchange during the five-year returns, 2008 to 2012, have been tested. The aim of the present research applied descriptive correlation. And to test hypotheses using panel data regression models are combined. Results of statistical analysis, hypothesis, research shows that between debt and cash flow sensitivity of investment is an inverse relationship And significant relationship between firm size and sensitivity and positive cash flow investment there. Also, the company's liquidity and cash flow sensitivity of investment is statistically significant and positive.